Investigating The Role Of Acceptance And Tolerance In Religious Communities (Journal of Namibian Studies : History Politics Culture, 2023)
In a more heterogeneous and linked world, the merits of embracing and accommodating different religious groups and society as a whole are essential in promoting concord, comprehension, and reciprocal regard among persons with varied views and origins. Swami Vivekananda, a prominent figure in the realm of spiritual ideology, articulated a deep philosophy that beyond the limitations of time, society, and belief systems. At the core of his teachings were the fundamental ideals of acceptance and tolerance, which he saw as essential foundations of a worldwide religion. This study paper examines the teachings of Swami Vivekananda to investigate the deep importance of acceptance and tolerance as fundamental elements of a global religion. By analyzing Vivekananda's works, lectures, and philosophical discourses, this study explains how acceptance goes beyond simple recognition and instead represents a deep embracing of religious diversity, while tolerance involves actively respecting the ideas and viewpoints of others.